2013
DOI: 10.1039/c2cp43555a
|View full text |Cite
|
Sign up to set email alerts
|

Holistic approach to dissolution kinetics: linking direction-specific microscopic fluxes, local mass transport effects and global macroscopic rates from gypsum etch pit analysis

Abstract: (2013) Holistic approach to dissolution kinetics : linking direction-specific microscopic fluxes, local mass transport effects and global macroscopic rates from gypsum etch pit analysis. Physical Chemistry Chemical Physics, Volume 15 (Number 6). pp. 1956pp. -1965pp. . ISSN 1463 Permanent WRAP url: http://wrap.warwick.ac.uk/54301/ Copyright and reuse:The Warwick Research Archive Portal (WRAP) makes the work of researchers of the University of Warwick available open access under the following conditions. Cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 79 publications
4
26
2
Order By: Relevance
“…However, (101) steps are less stable (Weijnen et al, 1987), and etch pits bounded by (001) and (100) are typically observed in the present study, based on the angles between the intersecting walls. Similar etch pit morphologies in gypsum have been reported by Fan and Teng (2007) and Peruffo et al (2013).…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…However, (101) steps are less stable (Weijnen et al, 1987), and etch pits bounded by (001) and (100) are typically observed in the present study, based on the angles between the intersecting walls. Similar etch pit morphologies in gypsum have been reported by Fan and Teng (2007) and Peruffo et al (2013).…”
Section: Resultssupporting
confidence: 86%
“…5, are (21 ± 2) pmol m −2 s −1 and (7.1 ± 4) µmol m −2 s −1 . These values are somewhat lower than, yet still basically consistent with, the surface normal rates of (40 ± 5) µmol m −2 s −1 , (50 ± 20) µmol m −2 s −1 , and (57 ± 14) µmol m −2 s −1 reported by Peruffo et al (2013), Colombani (2008), and Mbogoro et al (2011), respectively. Both ROI 1 and ROI 2 return to a lower rate of dissolution after the brief acceleration.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…[6][7][8][9][10][11][12] Studies of the mechanism and kinetics of dissolution processes are important for both fundamental understanding and for various technical applications. This area requires methodologies that can probe dissolution under conditions of high and well-defined mass transport, 13 so that surface kinetics can be extracted free from convolution from mass transport.…”
Section: Introductionmentioning
confidence: 99%